Rare diseases and orphan drugs in Eastern European Countries (Italian Journal of Public Health, 2009)
Background: Rare diseases are a serious public health problem. The countries of Eastern Europe are republicsin transition. Although many of them are already members of the EU and others could be further accepted, atthis stage it is difficult for local governments to spend money on rare diseases. The aim of this article is toreview current rare diseases and orphan drug activities in Eastern European countries (EEC).Methods: An extensive review of published literature and conference proceedings was undertaken in order toascertain the current status and ongoing activities in 10 Eastern European countries - Belarus, Bulgaria, CzechRepublic, Hungary, Moldova, Poland, Romania, Russia, Slovakia, and Ukraine. Data were collected andaggregated in 5 directions – information and awareness; diagnosis and screening practices; clinicalmanagement and rehabilitation; patient organizations and national plans on rare diseases.Results: The awareness and public health initiatives on rare diseases in Eastern European countries aregenerally low. EEC, which are also EU member states provide comparatively better healthcare services topeople with rare diseases in respect to clinical management, rehabilitation and access to orphan drugs.Patient associations are becoming more and more active, thus pushing local governments to consider EUlegislation and best practices on rare diseases. However, the gap between EEC and the rest EU member statesrequire intensive attention and support by the European commission, especially on improving awareness bytranslation of available information sources in local languages, and facilitating networking projects among allEuropean countries.
Keywords: rare diseases; orphan drugs; Eastern Europe; health policy